Enhanced generation of perfluoroalkyl carboxylic acids (PFCAs) from fluorotelomer alcohols (FTOHs) via ammonia-oxidation process. (May 2018) - Yu, Xiaolong; Nishimura, Fumitake; Hidaka, Taira
Abstract: With the phase-out of persistent, bioaccumalative, and toxic perfluoroalkyl carboxylic acids (PFCAs), it is needed to explore the potential release of PFCAs from precursors being emitted into the environment. Biotransformation of fluorotelomer alcohols (FTOHs) via biological processes in wastewater treatment plants (WWTPs) leads to discharge of PFCAs into receiving waters. However, the commonly existed microbial activity that can impact on FTOHs biodegradation in WWTPs remains unclear. The objective of present research was to explore the relationship between ammonia-oxidation process and the enhanced PFCAs generation from FTOHs biodegradation under aerobic activated sludge. The obtained results indicate that the cometabolism process performed by nitrifying microorganisms (NMs) was responsible for enhanced PFCAs generation. Among NMs, the ammonia-oxidation bacteria that can express non-specific enzyme of ammonia monooxygenases resulted in the enhanced PFCAs generation from FTOHs. Meanwhile, the different addition amount of ammonia contributed to different defluorination efficiency of FTOHs. The present study further correlated the enhanced PFCAs generation from FTOHs biodegradation with ammonia-oxidation process, which can provide practical information on effective management of PFCAs generation in WWTPs. Graphical abstract: Highlights: Cometabolism process influenced PFCAs generation from FTOHs in activated sludge. Generation of PFCAs and F − correlated negatively with ammonia addition amounts. Ammonia-oxidation bacteria played an essential role in enhanced PFCAs generation. Ammonia monooxygenases may be incorporated in FTOHs biodegradation.